Pharmacist Contributions to the U.S. Health Care System - Jon C. Schommer; Lourdes G. Planas; Kathleen A. Johnson; William R. Doucette; Caroline A. Gaither; David H. Kreling; David A. Mott (University of Minnesota Libraries Publishing, 2010)
Objective: The overall goal for this study was to conduct a segment analysis of the pharmacist workforce during 2009 based upon time spent in medication providing and in patient care services. Methods: Data for this study were obtained from the 2009 National Pharmacist Workforce Survey in which a random sample of 3,000 pharmacists was selected. Cluster analysis was used for identifying pharmacist segments and descriptive statistics were used for describing and comparing segments. Results: Of the 2,667 surveys that were presumed to be delivered to a pharmacist, 1,395 were returned yielding a 52.3% overall response rate. Of these, 1,200 responses were usable for cluster analysis. Findings from this study revealed five segments of pharmacists: (1) Medication Providers, (2) Medication Providers who also Provide Patient Care, (3) Other Activity Pharmacists, (4) Patient Care Providers Who also Provide Medication, and (5) Patient Care Providers. The results showed that, in 2009, 41% of U.S. pharmacists were devoted wholly to medication providing (Medication Providers). Forty-three percent of pharmacists contributed significantly to patient care service provision (Medication Providers who also Provide Patient Care, Patient Care Providers who also Provide Medication, and Patient Care Providers) and the remaining 16% (Other Activity Pharmacists) contributed most of their time to business / organization management, research, education, and other health-system improvement activities. Conclusions: Based on the findings, we propose that the pharmacy profession currently has, and will continue to build, capacity for contributing to the U.S. health care system in new roles for which they have been identified. However, as shifts in professional roles occur, a great deal of capacity is required related to new service provision. Resources are scarce, so an understanding of the most appropriate timing for making such changes can lead to cost-effective use of limited resources for improving patient care. Type: Original Research